Preparing Special Educators to Assume Collaborative and Consultative Roles - Long, Thomas J.; Brown, Carole; Nagy-Rado, Agnes (Catholic Education: A Journal of Inquiry and Practice, 2007)
The incidence of children with disabilities is growing in both the private and public school sectors. As a result of this trend and efforts to place children in inclusive settings, there is an increasing need for special educators who can provide instruction within the context of a regular education classroom, develop individualized education plans (IEPs), support parents, and be consultants to teachers on behalf of children. The consultative special education teacher will be increasingly in demand in the future if children with disabilities are to be successfully included in public, private, and Catholic schools. The Catholic University of America utilizes a consultative, collaborative model for preparing Master’s candidates in its special education program. The results of the first 4 years of this program demonstrate that the candidates in this program have acquired the knowledge, skills, and dispositions that are needed to be effective consultative, collaborative special educators in the field. This article provides a detailed description of the elements that make up this personnel preparation program. Particular focus is placed on the skills and knowledge to carry out consultative planning, including a rubric to evaluate the candidates’ performance. The article offers guidance to universities who may choose to create special education programs that prepare consultative special educators.